The unsung heroes: honouring the role of teachers in society - Abdul Razak, Mohd Abbas (Center for Community Development and Education (CCDE) Banda Aceh, Indonesia, 2025)
First and foremost, I would like to extend my heartfelt congratulations to all teachers who are devoted to their profession, regardless of the level they teach or the part of the world they come from. Teachers play a vital role in shaping the next generation of professionals and leaders. In recognition of the immense sacrifices they make, Teacher’s Day is celebrated around the world. This special occasion to honour educators is observed at different times of the year in various countries. In Malaysia, Teacher’s Day is celebrated annually on the 16th of May.